Development of gaming practices in popular science text - A. A. Bruev (Библиосфера)
The popular science text is described by the author in the context of competition with other media products: films, TV series, video games. Under these conditions, a popular science text acquires new communication characteristics, one of which is a play. The concept of play is viewed through the prism of Johan Huizinga’s work «Homo Ludens, a Study of the Play Element in Culture». The work highlights the main features of play. There are four such characteristics: a play brings pleasure, provides for the presence of special (play) behavior and establishes order, and is also characterized through the tension that arises in the process of playing activity. The play brings pleasure to the player, which in a popular science text is realized through the comprehension of new knowledge, as well as through the awareness of the abundance of sences and interpretations of the text, «flickering of meanings», realized with the help of metaphors. Play behavior is a «play with the addressee»: the use of professional vocabulary allows a reader to identify himself with a researcher. A special playful order is achieved through the use of special narrative schemes that makes it possible to avoid automatism in perception and help to assimilate the content of the text in the most productive way. The tension inherent to any play is interpreted as an intellectual tension associated with the comprehension of new sences, and as an emotional tension, which is achieved via the use of means of artistic expression and strengthens the reader’s emotional involvement in the events described in the text. Each statement is illustrated by examples from popular science works presented in the Russian book market. The author comes to the conclusion that modern popular science texts demonstrate a new property – a playful beginning.